INCREASING STUDENTS’ CONCEPT UNDERSTANDING CAPABILITY IN STATISTICS MATERIAL THROUGH THE DISCOVERY LEARNING MODEL: MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA MATERI STATISTIKA MELALUI MODEL DISCOVERY LEARNING - Pratiwi, Meitia Putri; Putra, Harry Dwi (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to determine the effect of the discovery learning model on high school students’ mathematical abilities. This type of research is classroom action research, which aims to increase educators’ professionalism in improving student learning outcomes. This research was carried out at senior high school Yumik Banjaran. The subjects in this research involved students in class XII IPA 1 for the 2023/2024 academic year with 36 students. The research instrument used was a description test during the pre-test and post-test. The learning material provided is data-centering statistical material. The tests carried out are divided into two parts, namely test cycles I and II (after giving the action). The procedures in this research consist of: (1) planning, (2) implementation of actions, (3) observation, and evaluation, and (4) reflection. The results of this research show that in cycle I the researcher was not optimal in providing understanding to students so there were still many students who did not understand the statistical material of data concentration, however in cycle II the researcher improved the learning method by paying more attention to the systematics in the discovery learning model so that after cycle II is completed, students’ mathematical understanding abilities can increase. Based on the performance indicators, it is concluded that students’ mastery of mathematical understanding in the data-centering statistics material for class XII IPA 1 students at senior high school Yumik Banjaran can be improved through the discovery learning model.